Cytokines in the blood of patients with type 2 diabetes mellitus depending on the level of overweight/obesity (literature review and own data) - K.P. Zak; V.V. Popova; V.L. Orlenko; O.V. Furmanova; N.D. Tronko (Mìžnarodnij Endokrinologìčnij Žurnal, 2021)
The paper analyzes the current literature data and the results of our own researches concerning the state of the cytokine network: pro- and anti-inflammatory cytokines (interleukin (IL) 1α, IL-1β, IL-4, IL-6, IL-10, IL-17 and tumor necrosis factor (TNF) α), α- and β-chemokines, including IL-8 and IL-16, as well as adipokines (leptin and adiponectin) in the peripheral blood of patients with type 2 diabetes (T2D) with normal and increased body weight/obesity. It has been shown that patients with T2D are characterized by an increased content of proinflammatory cytokines (IL-1, IL-6, IL-17, TNFα), α- and β-chemokines in the peripheral blood, including IL-8 and IL-16, as well as leptin with a decrease in adiponectin content. In lean patients (with body mass index (BMI) < 25.5 kg/m2) compared to lean normoglycemic individuals from the control group (BMI < 25.5 kg/m2), there is a small but significant increase in IL-1β, IL-6, IL-17, TNFα and leptin, which, as BMI increases, significantly increases in severe obesity (BMI > 30.0 kg/m2), especially in obese women (BMI > 35.0 kg/m2). Similarly, an increase in proinflammatory cytokines is observed in normoglycemic people, but not as significant as in T2D. Less clear data were obtained when during determination of the anti-inflammatory cytokines IL-4 and IL-10, which is explained by a significant polymorphism of their genes, and both protective and compensatory effects on pro-inflammatory cytokine rise. In T2D patients, especially those with obesity, there is an increase in the leptin level and a decrease in the adiponectin content. The severity of the course and the percentage of mortality are closely associated with the BMI of patients. The effectiveness of the fight against an increase in the incidence of T2D should be primarily aimed at preventing obesity, and in case of already developed T2D — at reducing concomitant obesity. The analysis of the data presented also suggests that a sharp increase in the content of pro-inflammatory cytokines (so called cytokine storm) observed in patients with T2D and obesity infected with COVID-19, is a consequence of the summation and potentiation of already existing inflammatory process.